Pembuatan Platform Retensi Dokumen Rekam Medis Rawat Jalan Berbasis Google Form - Elsa Tamara Okta Widyawati; Gunawan Rachmat (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Abstract. Retention of medical records is the activity of reducing medical records from active shelves to inactive shelves or electronic media by determining the storage period on the basis of their useful value. If retention is not carried out, there will be an accumulation of medical records in the active shelf, making storage and retrieval difficult which is an indicator of service quality. The purpose of this service is to help hospitals find priority problems in medical record unit services. Implementation time for 1 week. The method used is observation and interviews with medical record officers. The priority of the problem is determined through a focus group discussion (FGD) by determining the level of urgency, seriousness, and growth (UGD) of the problem. The priority issues obtained are; 1) the accumulation of inactive outpatient medical records, 2) it often happens that medical records are not found on the filing shelf during service, 3) medical records are brought by the patient's family after registering in the emergency room. The action solution is focused on overcoming the accumulation of inactive outpatient medical records, namely by creating an outpatient medical record retention system using Google Form media. The main target of the action is to assist three medical record officers in the filing division to understand using a google form-based retention model. The end result of the community service for all medical record officers at the hospital understands using a google form-based retention model. Keywords: Retention, Outpatient Medical Records, Google Form